Melatonin modulates wireless (2.45 GHz)-induced oxidative injury through TRPM2 and voltage gated Ca2+ channels in brain and dorsal root ganglion in rat - Naziroglu, M.; Celik, O.; Ozgul, C.; Cig, B.; Dogan, S.; Bal, R.; Pariente, J. A. (Pergamon-Elsevier Science Ltd, 2012)
We aimed to investigate the protective effects of melatonin and 2.45 GHz electromagnetic radiation (EMR) on brain and dorsal root ganglion (DRG) neuron antioxidant redox system. Ca2+ influx, cell viability and electroencephalography (EEG) records in the rat. Thirty two rats were equally divided into four different groups namely group A1: Cage control, group A2: Sham control, group B: 2.45 GHz EMR, group C: 2.45 GHz EMR+ melatonin. Groups B and C were exposed to 2.45 GHz EMR during 60 min/day for 30 days. End of the experiments, EEG records and the brain cortex and DRG samples were taken. Lipid peroxidation (LP), cell viability and cytosolic Ca2+ values in DRG neurons were higher in group B than in groups A1 and A2 although their concentrations were increased by melatonin, 2-aminoethyldiphenyl borinate (2-APB), diltiazem and verapamil supplementation. Spike numbers of EEG records in group C were lower than in group B. Brain cortex vitamin E concentration was higher in group C than in group B. In conclusion, Melatonin supplementation in DRG neurons and brain seems to have protective effects on the 2.45 GHz-induced increase Ca2+ influx, EEG records and cell viability of the hormone through TRPM2 and voltage gated Ca2+ channels. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Melatonin; Ca2+ influx; Dorsal root ganglion neuron; Electroencephalography records; Oxidative stress; TRPM2 channels; Wireless devices